2016
DOI: 10.3389/fpsyg.2016.00597
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gray Matter Volume and White Matter Integrity in College Students with Mobile Phone Dependence

Abstract: Mobile phone dependence (MPD) is a behavioral addiction that has become an increasing public mental health issue. While previous research has explored some of the factors that may predict MPD, the underlying neural mechanisms of MPD have not been investigated yet. The current study aimed to explore the microstructural variations associated with MPD as measured with functional Magnetic Resonance Imaging (fMRI). Gray matter volume (GMV) and white matter (WM) integrity [four indices: fractional anisotropy (FA); m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 62 publications
(97 reference statements)
2
37
2
1
Order By: Relevance
“…For example, some estimate that the average user checks their phone around 80 times per day (Asurion, ). Additionally, the beeps, buzzes, notifications, and messages may lead to dopamine responses or changes in the brain similar to that found in Internet addiction (e.g., Liu & Luo, ; Wang et al, ; Zhu, Zhang, & Tian, ; see Brand, Young, & Laier, for a review). In a sense, individuals are intermittently rewarded for their phone use, which may serve to further reinforce the behavior or create cravings for use.…”
Section: Why Do Parents Use Phones While With Children?mentioning
confidence: 88%
“…For example, some estimate that the average user checks their phone around 80 times per day (Asurion, ). Additionally, the beeps, buzzes, notifications, and messages may lead to dopamine responses or changes in the brain similar to that found in Internet addiction (e.g., Liu & Luo, ; Wang et al, ; Zhu, Zhang, & Tian, ; see Brand, Young, & Laier, for a review). In a sense, individuals are intermittently rewarded for their phone use, which may serve to further reinforce the behavior or create cravings for use.…”
Section: Why Do Parents Use Phones While With Children?mentioning
confidence: 88%
“…Moreover, the study report smaller GMV in right lateral orbitofrontal cortex in problematic smartphone users than controls (29). Another study also takes the VBM method and nd that decreased GMV of right superior frontal gyrus, right inferior frontal gyrus and bilateral thalamus in mobile phone dependence group (30). For mental disorders, a meta-analysis which included 41 studies has reported GMV difference in major depression compared to healthy controls including insula and anterior superior temporal gyrus (31).…”
Section: Discussionmentioning
confidence: 92%
“…Wykazano także zmniejszoną objętość zakrętu czołowego górnego, prawego dolnego zakrętu czołowego oraz wzgórza. Zakręt czołowy górny pełni funkcję w wielu zaawansowanych procesach poznawczych, takich jak: kontrola impulsów, świadome podejmowanie decyzji, pamięć, kontrola uwagi typu góra-dół oraz modelowanie i przewidywanie zachowań innych osób [58][59][60]. Prawy dolny zakręt czołowy jest odpowiedzialny za kontrolę zachowania [61].…”
Section: Neurobiology and The Genetics Of Mobile Phone Addictionunclassified
“…Furthermore, the superior frontal gyrus, right inferior frontal gyrus and thalamus volumes were demonstrated to be reduced. The superior frontal gyrus fulfils functions in many advanced cognitive processes like control of impulses, conscious decision-making, memory, top-down attentional control and the modelling and prediction of other person's behaviour [58][59][60]. The right inferior frontal gyrus is responsible for behaviour control [61].…”
Section: Neurobiology and The Genetics Of Mobile Phone Addictionmentioning
confidence: 99%